Науково-методичний підхід до обчислення оптимального рівня франшизи страховими компаніями України як складова систем управління ризиками промислових підприємств - Посохов, Ігор Михайлович; Іващенко, П. О.; Жадан, Юлія Володимирівна (Національний авіаційний університет, 2019)
У статті досліджено страхову модель нобелевського лауреата К. Ерроу у сучасних умовах економічного розвитку на прикладі двох вітчизняних галузей – машинобудування (класична галузь) та олійно-жирової галузі (сучасна галузь, що стрімко розвивається). Проаналізовано сучасний стан страхового ринку України та розроблено науково-методичного підходу до обчислення оптимального рівня франшизи українськими страховими компаніями. Запропоновано науково-методичний підхід до обчислення оптимального рівня франшизи страховими компаніями України як складову систем управління ризиками промислових підприємств. Зроблено висновок, що використання запропонованого науково-методичного підходу до обчислення оптимального рівня франшизи страховими компаніями України дозволить оптимізувати рівень франшизи для рівномірного розподілу випадкових збитків підприємства та мінімізувати ризики самих страхувальників, а також вдосконалити методологію управління ризиками промислових підприємств та страхових компаній.

In conditions of uncertainty of the economy, changes of property forms and management mechanism in the economy need of economic entities in protecting their property interests and the interests of employees from a variety of risks is growing. The state is also interested in insurance protection of state property and improving socio-economic security of the citizens of Ukraine. That is why it is very relevant to consider the insurance model of the Nobel Prize Laureate K. Arrow in modern economic development on the example of two domestic industries – mechanical engineering (classical industry) and oilfatty sector (a rapidly growing modern industry). Analyzed the current state of the Ukrainian insurance market and develop a scientific and methodical approach to calculating the optimal level of franchise by insurance companies of Ukraine. The survey is based on the model of the Nobel laureate K. Arrow, taking into account the specifics of the insurance industry and selected industries for research. The result of the article is the development of the approach to calculating the franchise, based on the benefits of the client or insurance company. The correlation proposed by the author represents the insurance politic of the insurance company. Using the proposed scientific and methodological approach to calculating the optimal level of franchise by insurance companies of Ukraine, will allow to optimize franchise level for the uniform distribution of casualties enterprises and minimize the risks of the insurers themselves and improve the methodology of risk management of industrial enterprises and insurance companies. The conditions of coincidence of the optimal level of franchise with the mathematical expectations of random losses of the enterprise are established. The formula for calculating the optimal level of franchise for the equable distribution of random losses of the enterprise is proposed; the behavior of the optimal level of franchise in the case of an increase in the size of the interval of the equable distribution of random losses of the enterprise is analyzed; a linear correlation between the optimal franchise level and the right end of the interval of the equable distribution of random losses of the enterprise is obtained.
The scientific and methodical approach to calculating the optimum level of the franchise by Ukrainian insurance companies as a component of risk management systems for industrial enterprises
Keywords: ризики; управління ризиками; страховий ринок України; франшиза; рівномірний розподіл; випадкові збитки підприємства; risk; risk management; insurance market of Ukraine; franchise; uniform distribution; accidental damage to the enterprise